Parental Perception of the Impact of Television Advertisements on Children’s Buying Behavior: A Case of Kathmandu Valley - Singh, Sashish (Nepalese Journal of Finance, 2024)
This study examines the parental perception of the impact of television advertisements on children’s buying behavior in Kathmandu Valley. Buying behaviour is the dependable variable. The independent variables are television advertisement, marketing, child responsiveness, price, taste and parent potential. The primary source of data is used to assess the opinions of the respondents regarding the parental perception of the impact of television advertisements on children’s buying behavior in Kathmandu Valley. The study is based on primary data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of television advertisement, marketing, child responsiveness, price, taste and parent potential on children’s buying behavior in Kathmandu Valley. The study showed that television advertisement has a positive impact on buying behaviour. It indicates that creative and innovative television advertisement impulse children buying behavior. Similarly, marketing has a positive impact on buying behaviour. This implies that effective marketing concerning children’s stimulates children buying behavior. Likewise, child responsiveness has a positive impact on buying behaviour. It indicates that child responsiveness content on the advertisement impulse children buying behavior. Similarly, parental potential has a positive impact on buying behaviour indicating that parental potential stimulates children buying behavior. Moreover, price has a positive impact on buying behaviour. It indicates that higher price for the product stimulates children buying behavior. Similarly, taste has a positive impact on the buying behavior. It shows that the good taste attracts children to buy products. The regression result also that beta coefficients are significant for television advertisement, price, parental potential and taste at one percent level of significance.